2013
DOI: 10.1080/00049158.2013.848509
|View full text |Cite
|
Sign up to set email alerts
|

Assessing sustainability in certification schemes

Abstract: This paper aims to provide guidance as to how better to assess sustainability in certification schemes, such as the Australian Forestry Standard, and to provide suggestions for related changes to certification guidelines.The meaning of sustainability in relation to forestry and the principles underpinning sustainability and the calculation of sustained yield are examined to see how best they can be assessed in certification schemes, given the complexities of temporal and spatial change. To be useful in certifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A survey of the literature reveals a wide range in the length of simulation chosen to investigate the sustainability or consequences of timber harvesting (excluding studies of species succession), and reveals few explanations for the length chosen. Hoogstra and Schanz (2009) suggested that 15 years is the most distant horizon that is realistic for most foresters, and Ferguson (2013) argued that planning horizons beyond 50 years stretch credulity, a contrast to earlier suggestions (e.g., Botkin 1993) that 400-year studies may be needed to infer sustainability. It is common for the planning horizons of yield forecasts to span 60 (e.g., Howard andValerio 1996, Harper et al 2007) to 100 years (e.g., McKenney 1990, Vanclay 1994, Rohweder et al 2000, Baskent and Keles 2005 or 2-3 harvesting cycles (e.g., Preston and Vanclay 1988, Weintraub et al 1994, Vanclay 1996), while some studies in tropical forests may deal with intervals as long as 400-500 years (e.g., Huth andDitzer 2001, Sebbenn et al 2008).…”
Section: Empirical Examples Of Planning Horizonsmentioning
confidence: 97%
“…A survey of the literature reveals a wide range in the length of simulation chosen to investigate the sustainability or consequences of timber harvesting (excluding studies of species succession), and reveals few explanations for the length chosen. Hoogstra and Schanz (2009) suggested that 15 years is the most distant horizon that is realistic for most foresters, and Ferguson (2013) argued that planning horizons beyond 50 years stretch credulity, a contrast to earlier suggestions (e.g., Botkin 1993) that 400-year studies may be needed to infer sustainability. It is common for the planning horizons of yield forecasts to span 60 (e.g., Howard andValerio 1996, Harper et al 2007) to 100 years (e.g., McKenney 1990, Vanclay 1994, Rohweder et al 2000, Baskent and Keles 2005 or 2-3 harvesting cycles (e.g., Preston and Vanclay 1988, Weintraub et al 1994, Vanclay 1996), while some studies in tropical forests may deal with intervals as long as 400-500 years (e.g., Huth andDitzer 2001, Sebbenn et al 2008).…”
Section: Empirical Examples Of Planning Horizonsmentioning
confidence: 97%
“…It has been known that volume is widely used to measure the amount of wood in the processes of estimating the economic value or commercial utilization (Ferguson, 2013). It has been reported that the tree volume, which is estimated from the measured DBH is used to determine the forest structure (Picard et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The former should be geared to measurable outcomes over shorter timescales. The long-term sustainability goals are more aspirational but require review at the conclusion of the maturity period (see Ferguson [21]). The Plan should allow for periodic review and revision, linked to continuing verification and certification.…”
Section: Management Planmentioning
confidence: 99%